Immobilized humic substances and immobilized aggregates of humic substances as sorbent for solid phase extraction - Erny, Guillaume L. (2018)
In this work, humic substances (HS) immobilized, as a thin layer or as aggregates, on silica gel were tested as material for solid phase extraction. Some triazines (simazine, atrazine, therbutylazine, atrazine-desethyl-desisopropyl-2-hydroxy, ametryn and terbutryn), have been selected as test analytes due to their environmental importance and to span a large range of solubility and octanol/water partition coefficient (logP). The sorbent was obtained immobilizing a thin layer of HS via physisorption on a pre-coated silica gel with a cationic polymer (polybrene). While the sorbent could be used as it is, it was demonstrated that additional HS could be immobilized, via weak interactions, to form stable humic aggregates. However, while a higher quantity of HS could be immobilized, no significant differences were observed in the sorption parameters. This sorbent have been tested for solid phase extraction to concentrate triazines from aqueous matrixes. The sorbent demonstrated performances equivalent to commercial alternatives as a concentration factor between 50 and 200, depending on the type of triazines, was obtained. Moreover the low cost and the high flow rate of sample through the column allowed using high quantity of sorbent. The analytical procedure was tested with different matrixes including tap water, river water and estuarine water.